2022
DOI: 10.1101/2022.03.13.22272317
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A shared genetic signature for common chronic pain conditions and its impact on biopsychosocial traits

Abstract: Background: The multifactorial heterogenous nature of chronic pain with its multiple comorbidities presents a formidable challenge in disentangling the aetiology underlying patient symptoms. Methods: Here, we performed genome-wide association studies (GWAS) of eight types of regional chronic pain using UK Biobank data (N=4,037-79,089 cases; N=239,125 controls), followed by bivariate linkage disequilibrium-score regression and latent causal variable analyses to determine (respectively) their genetic correlation… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 90 publications
0
1
0
Order By: Relevance
“…In the previous studies, patients with lower socioeconomic status have been found to be more symptomatic, with worse pain outcomes, and more depression 35 . People with higher education usually have a better income level, they tend to seek treatment at an earlier stage after the onset of LDH, and they often have better pain management methods and generally healthier lifestyles 35,36 . Additionally, we noted a potential causal relationship between LDH and the frequency of tiredness in last two weeks (beta=0.02, pFDR=0.046, Fig.…”
Section: Main Textmentioning
confidence: 89%
“…In the previous studies, patients with lower socioeconomic status have been found to be more symptomatic, with worse pain outcomes, and more depression 35 . People with higher education usually have a better income level, they tend to seek treatment at an earlier stage after the onset of LDH, and they often have better pain management methods and generally healthier lifestyles 35,36 . Additionally, we noted a potential causal relationship between LDH and the frequency of tiredness in last two weeks (beta=0.02, pFDR=0.046, Fig.…”
Section: Main Textmentioning
confidence: 89%